Open innovation and user s involvement in new product development: a case study in the automotive sector - Mazini, Sérgio Ricardo [UNESP]; Gobbo Junior, José Alcides [UNESP]; Jugend, Daniel [UNESP]; Silva, Sérgio Luis da (Editora Cubo, 2013)
Innovation is an essential factor for obtaining competitive advantages. The search for external knowledge sources for product creation, which can contribute to the innovation process, has become a constant among companies, and users play an important role in this search. In this study, we aimed to analyze user’s involvement in the product development process based on open innovation concepts. We used the unique case study research method. This study was carried out in an automotive company that has developed a project of a concept car involving user’s through the Web 2.0. With such scope, the research demonstrates that users can contribute not only with generation of ideas but also with the innovation process itself.
Keywords: Open innovation; User driven innovation; New product development